2000
DOI: 10.1177/136140960000500111
|View full text |Cite
|
Sign up to set email alerts
|

Role perceptions of auxiliary nurses: An exploratory study

Abstract: Auxiliary nurses may form a necessary part of current nursing teams, but how clear are they about their roles, capabilities and limitations? The project described in this paper was divided into two phases: Phase 1 involved interviews with auxiliary nurses and corresponding G grade nurses; Phase two involved distribution of questionnaires to over 350 auxiliary nurses in nine hospitals across the Yorkshire region. This paper focuses on Phase 2 only. The questionnaire was developed from both the literature and Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…One further disconcerting finding was the suggestion, implicitly and explicitly, that the role of the qualified nurse probably can be effectively carried out by unqualified staff and the main difference is giving of medication. The sentiment of the only difference in qualified nurses and auxiliary nurses' work was giving out drugs that was indicated in a study with auxiliary nurses (Pearcey 2000). Gonzalez-Torre et al (2002) suggest that nursing work needs to be matched to patients' needs to ensure quality is not lost; they provide a model for 'minimum' staff calculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One further disconcerting finding was the suggestion, implicitly and explicitly, that the role of the qualified nurse probably can be effectively carried out by unqualified staff and the main difference is giving of medication. The sentiment of the only difference in qualified nurses and auxiliary nurses' work was giving out drugs that was indicated in a study with auxiliary nurses (Pearcey 2000). Gonzalez-Torre et al (2002) suggest that nursing work needs to be matched to patients' needs to ensure quality is not lost; they provide a model for 'minimum' staff calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion is promoted both through empirical findings (Irvine et al 1998, Gonzalez-Torre et al 2002, Doran et al 2002, BJN 2004, Keeney et al 2005, Atwal et al 2006) and discourse (Kosinska & Niebró j 2003, Hewitt-Taylor 2003, Scott 2004, Thompson & Watson 2005, Shields & Watson 2007 with the suggestion that the role of the qualified nurse is difficult to encapsulate. This is exacerbated by the perpetually increasing expansion of clinical nursing roles and the delegation of nursing work to health care assistants (Draper 1990, Woodward 1997, Pearcey 2000, Wakefield 2000, Spilsbury & Meyer 2005, McKenna et al 2006. The literature cited here suggests this is not an issue confined to the UK as the foregoing publications represent views from Spain, Poland, Canada and the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, despite national support for HCA training in the UK (DoH 2000a(DoH , 2000b, studies have indicated the need to identify the impact of the role (Pearcy 2000, Fletcher & Rush 2001, Bowman et al 2003. Until relatively recently, the UK had two levels of clinical nurse -Registered Nurse and Enrolled Nurse.…”
Section: Staff and Patient Satisfactionmentioning
confidence: 99%
“…Although several researchers have investigated the HCA role Workman 1996, Pearcy 2000, Thornley 2000), confusion remains about its parameters, and the line between nursing and non‐nursing duties continues to be blurred. The role is not standardized and depends on many factors, including the particular clinical area, methods of delegation and ideologies of the health care setting (Ahmed & Kitson 1993a, Chang & Lam 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…Expertise and experience are as valuable to clinical practice as to patient outcomes (Santy, 2001) but the empirical basis for this is not greatly evident in orthopaedic nursing (Kneale and Knight, 1997). Pearcey (2000) warns that decision making about aspects of patient care must remain the responsibility of those qualified to do it.…”
Section: Literature Reviewmentioning
confidence: 99%